SOSIALISASI PRODUK HALAL UNTUK MENINGKATKAN KREATIVITAS UMKM DAN INTERPERSONAL PESERTA DIDIK SDN TANJUNG HARAPAN, MERBAU MATARAM, LAMPUNG SELATAN: PENDEKATAN METODE PARTICIPATORY ACTION RESEARCH - Mardiansyah, Feby Valentin; Wiliyanti, Vandan; Gunawan, Indra; Khoiriyah, Solatun (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2024)
Halal product socialization is important in the context of education at SDN Tanjung Harapan. Halal is not only related to religious aspects, but also has an impact on increasing creativity in micro, small and medium enterprises (MSMEs) managed by students. This study aims to explore the impact of halal product socialization on the intrapersonal creativity of SDN Tanjung Harapan students. This study aims to increase the intrapersonal creativity of Tanjung Harapan State Elementary School (SDN) students in Market Day activities. Market Day is an activity where learners create products or services that are sold to students, teachers, and parents at school. This research was conducted to develop learners' creativity in producing innovative and interesting products or services. The activities carried out were attended by grades 4-6 of Tanjung Harapan Elementary School as an effort to train entrepreneurship as early as possible. This activity is the result of the work program carried out by KKN UIN Raden Intan Lampung members in Tanjung Harapan village, Merbau Mataram, South Lampung. This research uses the Participatory Action Research (PAR) method which involves collaboration between researchers and students of SDN Tanjung Harapan. The research steps include: a. Problem identification: Identify the needs of students in understanding halal products. b. Action planning: Designing a halal product socialization program that is suitable for the level of understanding of students. c. Implementation: Implement the socialization program and observe changes in the understanding and creativity of students. d. Evaluation: Analyzing the results of the socialization program and formulating recommendations. The results of the discussion show that after the socialization of halal products, students' understanding of halal products has increased significantly. In addition, this program also has a positive impact on learners' intrapersonal creativity. They are more aware of the importance of halal products in their MSME business, and this inspires them to create more innovative and quality products. In its implementation, there are 3 stages to make the event successful, namely the planning and preparation stage, then the execution or implementation stage and then evaluation. Based on the results of the study, it can be concluded that the socialization of halal products has a positive impact on the intrapersonal creativity of students of SDN Tanjung Harapan. A better understanding of halal products encourages learners to develop creative ideas in their MSME businesses. Therefore, it is important to continue encouraging halal product socialization programs in education to support the development of more creative and ethical MSMEs in the future.